Capacity constraining labor market frictions in a global economy - Christian Holzner; Mario Larch (Center for Economic Studies and ifo Institute (CESifo), 2011)
Convex vacancy creation costs shape firms' responses to trade liberalization. They induce capacity constraints by increasing firms' cost of production, leading a profit maximizing firm not to fully meet the increased foreign demand. Hence, firms will only serve a few export markets. More productive firms will export to more countries and charge higher or similar prices compared to less productive firms. Trade liberalization also affects labor market outcomes. Increased profits by exporting firms triggers firm entry, reduces unemployment and increases wage dispersion in the on-the-job search model with monopolistic competition.
Keywords: F16; F12; J64; L11; 330; on-the-job search; capacity constraints; international trade; heterogeneous firms; monopolistic competition